Death beyond disavowal : the impossible politics of difference - Hong, Grace Kyungwon (Difference incorporated., 2015)
'Death Beyond Disavowal' utilises 'difference' as theorised by women of colour feminists to analyse works of cultural production by people of colour as expressing a powerful antidote to the erasures of contemporary neoliberalism.